2012
DOI: 10.3389/fpls.2012.00015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics as a Hypothesis-Generating Functional Genomics Tool for the Annotation of Arabidopsis thaliana Genes of “Unknown Function”

Abstract: Metabolomics is the methodology that identifies and measures global pools of small molecules (of less than about 1,000 Da) of a biological sample, which are collectively called the metabolome. Metabolomics can therefore reveal the metabolic outcome of a genetic or environmental perturbation of a metabolic regulatory network, and thus provide insights into the structure and regulation of that network. Because of the chemical complexity of the metabolome and limitations associated with individual analytical plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 50 publications
1
75
0
Order By: Relevance
“…These data are consistent with previous studies of these inbreds that identified Mo17 mature seeds having a higher amino acid content than B73 seeds (Römisch-Margl et al, 2010). As the germination process proceeds, these differences in amino acid content between the two inbreds is reduced, so that by 36 h postimbibition, the profiles are almost identical except for Lys, Thr, and Arg, which are still slightly higher in Mo17, and Trp, which is now slightly higher in B73 (Supplemental Fig.…”
Section: Analysis Of the Metabolomes Of Germinating Seedssupporting
confidence: 82%
See 1 more Smart Citation
“…These data are consistent with previous studies of these inbreds that identified Mo17 mature seeds having a higher amino acid content than B73 seeds (Römisch-Margl et al, 2010). As the germination process proceeds, these differences in amino acid content between the two inbreds is reduced, so that by 36 h postimbibition, the profiles are almost identical except for Lys, Thr, and Arg, which are still slightly higher in Mo17, and Trp, which is now slightly higher in B73 (Supplemental Fig.…”
Section: Analysis Of the Metabolomes Of Germinating Seedssupporting
confidence: 82%
“…For those compounds observed only in two data sets, the missing values were replaced by one-third of the estimated minimum value. Log 2 -ratio plots were calculated for each metabolite as described previously (Quanbeck et al, 2012). The raw data and averages and SE calculations were determined from three biological replicates and are available in the PMR database and Supplemental Tables S2 to S4, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Log 2 ratios and SE were calculated as described previously (Quanbeck et al, 2012). Metabolomic data were deposited in the PMR database (Hur et al, 2013) under accession number mtFAS.…”
Section: Metabolomic Analysesmentioning
confidence: 99%
“…As an untargeted approach to gain a broad overview of the complexity of plant metabolic composition, the technology has, in a short time, made significant inroads into helping expand our knowledge of plant biochemistry (Kueger et al, 2012;Etalo et al, 2013;Hunerdosse and Nomura, 2014;Meret et al, 2014). Typically, rich metabolomics data sets already provide us with a valuable means to generate hypotheses relating to plant metabolism, which then become the focus of further, more direct investigation (Quanbeck et al, 2012). New technologies are being developed, and especially, new data-mining strategies are being designed to allow us to look deep into plant metabolism without having first to rely on preconceptions.…”
mentioning
confidence: 99%